Perancangan Fasilitas Pabrik Tahu untuk Meminimalisasi Material Handling - Siska, Merry; Henriadi, H (Jurnal Teknik Industri, 2012)
UD. Dhika Putra is a tahu manufacturing company. Currently, the company is having some problems in production facility layout and physical environment. This study aimed to redesign the facility layout of tahu manufacturing company to minimize the path length of material handling and apply the 55 method to enhance work productivity. The approach used to redesign the plant facility layout is Systematic Layout Planning (SLP), which can be categorized in three stages, namely material flow analysis, research, and selection. While the 55 method consist of several steps to organize workplace condition that affect on the effectiveness, eficiency, productivity, and safety. This study concluded that the chosen layout for the final layout showed a significant decrease in path length of material handling, i.e 45 meters or about 19,2%. The decreasing of material handling path length on the choosen layout was also influenced by the arrangement of the work place by using 55 method.Â